Citrin and aralar1 are Ca(2+)-stimulated aspartate/glutamate transporters in mitochondria - Palmieri, L. (Oxford University Press, 2001)
The mitochondrial aspartate/glutamate carrier catalyzes an important step in both the urea cycle and the aspartate/malate NADH shuttle. Citrin and aralar1 are homologous proteins belonging to the mitochondrial carrier family with EF-hand Ca(2+)-binding motifs in their N-terminal domains. Both proteins and their C-terminal domains were overexpressed in Escherichia coli, reconstituted into liposomes and shown to catalyze the electrogenic exchange of aspartate for glutamate and a H(+). Overexpression of the carriers in transfected human cells increased the activity of the malate/aspartate NADH shuttle. These results demonstrate that citrin and aralar1 are isoforms of the hitherto unidentified aspartate/glutamate carrier and explain why mutations in citrin cause type II citrullinemia in humans. The activity of citrin and aralar1 as aspartate/glutamate exchangers was stimulated by Ca(2+) on the external side of the inner mitochondrial membrane, where the Ca(2+)-binding domains of these proteins are localized. These results show that the aspartate/glutamate carrier is regulated by Ca(2+) through a mechanism independent of Ca(2+) entry into mitochondria, and suggest a novel mechanism of Ca(2+) regulation of the aspartate/malate shuttle.